Influence of laser shock peening on the residual strains and stresses in additively manufactured TC4 (Fracture and Structural Integrity, 2025)
Additively manufactured materials possess significant heterogeneities and anisotropies of stiffness and strength properties between the growth and transverse directions. Residual stresses induced by the fabrication and processing stages are critical to the service life of these materials. In this work, an experimental study of the residual stress fields was conducted in samples cut from additively manufactured titanium alloy TC4. The depth profiles of residual elastic strains for various regimes of laser impact treatment were obtained on elementary samples in the form of rectangular plates of 100´20´5 mm. Five treatment regimes were studied by varying the laser power density, the spot shape, and the percentage of overlap. The dependence of relief strains and residual stress levels on the laser energy density was obtained for two laser spot shapes: a 1´1 mm square and a 2 mm diameter circle. The numerical model, validated against experimental data for both as-built and laser-peened states, provides a reliable tool for analyzing the residual stresses and strain in additively manufactured components.
Keywords: Additively manufactured TC4; Residual strains; Residual stresses; Laser shock peening